Régimen jurídico de los espacios marítimos de Spitzberg (Svalbard). Posición de Noruega, España y otros Estados (Revista Española de Derecho Internacional, 2007)
The Paris Treaty of 9th February 1920 put an end to the international terra nullius situation that had prevailed for one hundred years over the Archipelago of Spitsbergen in the most northern part of the world in the middle of the Artic Ocean. This change was possible due to the accommodation of the interests of the High Contracting Powers, who recognised the full and absolute sovereignty of Norway over the Archipelago of Spitsbergen under the restrictive conditions imposed in the Treaty. The sovereignty is limited by fishing and hunting rights and by liberties of access, anchorage and establishment of maritime, industrial, mining or commercial companies in the territories described in article 1 and in the territorial waters adjacent to them. Nevertheless, the greatest restriction on Norway’s sovereignty is established in article 9, by which Norway undertakes not to create and not to allow any naval base to be established in the regions set forth in the First Article and not to construct any fortification in these regions, which may not ever be used for warlike purposes. One of the main characteristics of the 1920 Paris Treaty is that the ships and nationals of the High Contracting Powers have ownership of the rights and liberties and not the High Contracting Powers themselves. The 1920 Paris Treaty, due to its objective and purpose, is still in force and it is compatible with the development of the Law of the Sea. As a result, the islands, except for rocks that are not suitable for maintaining human inhabitation or their own economic life, generate all the maritime spaces included in the Exclusive Economic Zone and the continental shelf. However, as the Paris Treaty is in force, Norway has not been able to establish an Exclusive Economic Zone around the Archipelago of Spitsbergen and it has been forced due to pressure from the majority of the High Contracting Powers to establish a non-discriminatory Fisheries Protection Zone with the same characteristics established in the second paragraph of article 2 of the Treaty. Respect for the archipelago’s continental shelf, the Norwegian Government’s official position and the doctrine that supports the official nature of this position do not accept that the Paris Treaty can apply to this continental shelf. A contrary position is maintained by the majority of the High Contracting Powers to the point of creating an opinio iuris on the possibility of applying the Paris Treaty to the continental shelf of Spitsbergen as a natural extension of the territories included in article 1, although the rights of exploration and exploitation of the natural resources would have to be in line mutatis mutandi with the provisions in Part 6 of the 1982 United Nations Convention on the Law of the Sea.